Exploring the potential of seaweed derivatives for the development of biodegradable plastics: A comparative study - Wan Amnin, Wan Yahaya; Nurul Aini, Mohd Azman; Fatmawati, Adam; Sarmilaah Dewi, Subramaniam; Khadijah Husna, Abd Hamid; Almajano, María Pilar (MDPI, 2023)
Biodegradable films made from biopolymer materials have the potential to replace conventional plastics, which can reduce waste disposal problems. This study aims to explore the potential of different seaweed derivate films consisting of 2% (w/w) of kappaphycus alverezi (KA), kappa carrageenan (KC), refined carrageenan (RC) and semi-refined carrageenan (SRC) as bio-based materials with 0.9% (w/w) glycerol (G), and reinforced with different concentrations of cellulose nanofibers (CNFs) derived from palm waste. A characterization of the glycerol-plasticized seaweed derivatives containing 0, 5, 10, and 15% (v/w) cellulose nanofiber is carried out. The CNFs were studied based on their mechanical, physical and thermal properties including mechanical properties, thickness, moisture content, opacity, water solubility, water vapor permeability and thermal stability. The hydrogen bonding was determined using the DFT calculation generated by Gauss view software version 9.6. The KA + G + 10%CNF film exhibited a surface with slight cracks, roughness, and larger lumps and dents, resulting in inferior mechanical properties (18.50 Mpa), making it unsuitable for biofilm production. The KC + G + 10%CNF film exhibited mechanical properties 24.97 Mpa and water vapor permeability of 1.42311 × 10−11 g s−1 m−1 Pa−1. The RC/G/10%CNF film displayed the highest TS (48.23 MPa) and water vapor permeability (1.4168 × 10−11 g s−1 m−1 Pa−1), but it also had higher solubility in water (66%). In contrast, the SRC + G + 10%CNF film demonstrated excellent mechanical properties (45.98 MPa), low water solubility (42.59%), low water vapor permeability (1.3719 × 10−11 g s−1 m−1 Pa−1), and a high decomposition temperature (250.62 °C) compared to KA, KC and RC. These attributes develop films suitable for various applications, including food packaging with enhanced properties and stability.